THE EFFECTIVENESS OF CLOPIDOGREL AS AN ANTITHROMBOTIC COMPARED TO TICLOPIDINE AND ASPIRIN (META-ANALYSIS) - Titien Siwi Hartayu; Dewi Setyaningsih (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2017)
Clopidogrel, an antithrombotic drug, has been proven by FDA as Plavix was initially used for the prevention of vascular occlusive that cause of myocardial infarction, stroke, and vascular death in patients with atherosclerosis and then it is used to treat Acute Coronary Syndrome (ACS). Aim of the study is to compare the effectiveness of Clopidogrel to aspirin and ticlopidine by meta-analysis of CLASSICS (The Clopidogrel Aspirin Stent International Cooperative Study), MATCH trial dan CAPRIE trial. Results of the study show that the effectiveness of Clopidogrel is significantly higher, however the risk of ischemic and bleeding is lower than aspirin and ticlopidine. Cost-effectiveness of Clopidogrel in avoiding secondary stroke in one episode is approximately US $ 33,000, and aspirin is only US $ 1400. In Indonesia the price of Clopidogrel is ranged from US $1.5 to US $3 each tablet, while the price of aspirin ranged from US $ 0.35 to US $ 0.72. However, in Indonesia Clopidogrel is now in the list of National Formulary, this fact might have contributed to the increasing use of Clopidogrel, which has reached around 1000 tablets per day in each hospital while aspirin has reached almost 1500 tablets per day.